Ruang Budaya “Barikan” Di Desa Sumber Polaman Lawang Jawa Timur - Fifi Damayanti; Agung Murti Nugroho; Herry Santosa (RUAS (Review of Urbanism and Architectural Studies), 2017)
Lawang city has many interesting sights, one of which is the source Polaman Baths, located in Sumber Polaman. In the Village of Polaman there are some cultural activities that make up the cultural space. Local communities do village ritual ceremonies to honor ancestors founders of the village as well as a petition to God for the prosperity of rural communities Polaman. The cultural activities are known as cultural ritual barikan. Time and Barikan ritual space in the traditional settlement pattern forming Polaman rural communities. The research method in this study is descriptive-qualitative method with an etnographic approach. This study aims to identify patterns formed by the settlement of the cultural activities that make up the cultural space. By knowing the settlement pattern is formed it will be determined the shape of preservation suitable for spaces used settlements and cultural preservation barikan itself.Keywords: cultural space, barikan traditional ceremonies, village Source Polaman